Abortion and Unborn Human Life, Second Edition - Lee, Patrick, 1952- (Book collections on Project MUSE., 2010)
"A very good book on the abortion question. Lee's methods are rigorous and exact, his writing accessibly clear. This book is, therefore, an especially welcome contribution to a field of enquiry in which these two qualities are rarely found in combination."--Jacket.